2001
DOI: 10.1007/s101510070012
|View full text |Cite
|
Sign up to set email alerts
|

Stapling procedure for haemorrhoids versus Milligan-Morgan haemorrhoidectomy: randomised controlled trial

Abstract: Surgical haemorrhoidectomy has a reputation for being a painful procedure for a fairly benign disorder. The circular transanal stapled technique for the treatment of haemorrhoids has the potential to achieve a less painful rectal procedure in place of ablative perianal surgery. We compared the short-term outcome of the circular stapled procedure for haemorrhoids with current standard surgery in a randomised controlled trial. Forty patients admitted for surgical treatment of prolapsing haemorrhoids were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 20 publications
3
65
1
4
Order By: Relevance
“…Our trial confirms the reduction in postoperative pain following SA reported by previous researchers7 8 10 11 and demonstrates a reduced analgesic requirement and a significantly earlier total pain resolution in these patients. Despite this significantly reduced pain, the patients who underwent SA in our trial did not return to work earlier and had a similar day surgery rate as the haemorrhoidectomy patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our trial confirms the reduction in postoperative pain following SA reported by previous researchers7 8 10 11 and demonstrates a reduced analgesic requirement and a significantly earlier total pain resolution in these patients. Despite this significantly reduced pain, the patients who underwent SA in our trial did not return to work earlier and had a similar day surgery rate as the haemorrhoidectomy patients.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of an external wound together with its proven reduced postoperative pain7 8 offers scope for early rehabilitation and may result in better patient satisfaction and improved uptake of day-case operations. Furthermore, the principles of reduction of the prolapsed anal cushion instead of its excision, interruption of the haemorrhoidal arterial pedicles during stapling, and control of the external components by an indirect pulling-up effect and reversing the effects of prolapse caused by vascular disruption may provide a more rational approach to addressing the disease in a broader group of patients, and may achieve a better physiological outcome 6.…”
mentioning
confidence: 99%
“…10 11 This technique potentially provides a tool for reducing some of the complications associated with conventional surgery, provided that the operator has the technical experience. However, stapling increases operative costs; advanced surgical skills are necessary; and there is a learning curve 12.…”
mentioning
confidence: 99%
“…Surgical approaches also need re-evaluation, taking into account the intensity of patients' pain. Endorectal mucosectomy is a less painful surgical technique, 23,24 and further prospective studies are necessary to evaluate its effectiveness in association with PPB for postoperative analgesia. Further studies may be also useful to compare pre-and postoperative PPB and to test the hypothesis of a pre-emptive analgesic effect.…”
Section: Discussionmentioning
confidence: 99%